2014
DOI: 10.1038/ejhg.2014.267
|View full text |Cite
|
Sign up to set email alerts
|

Consent procedures in pediatric biobanks

Abstract: The inclusion of children's samples in biobanks brings forward specific ethical issues. Guidelines indicate that children should be involved in the consent procedure. It is, however, unclear how to allocate an appropriate role for children. Knowledge of current practice will be helpful in addressing this issue. Therefore, we conducted an international multiple-case study on the child's role in consent procedures in pediatric biobanks. Four biobanks were included: (1) LifeLines, (2) Prevention and Incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The recommendations aim to strike this balance by including principles such as subsidiarity, the paediatric rule, the protection of minors and the minimisation of burden 22. Special considerations were given to the integration of minors in the consenting process 32. While consent is obtained from the legal guardian, minors have to be appropriately informed and have to have a voice in the decision-making process 33.…”
Section: Discussionmentioning
confidence: 99%
“…The recommendations aim to strike this balance by including principles such as subsidiarity, the paediatric rule, the protection of minors and the minimisation of burden 22. Special considerations were given to the integration of minors in the consenting process 32. While consent is obtained from the legal guardian, minors have to be appropriately informed and have to have a voice in the decision-making process 33.…”
Section: Discussionmentioning
confidence: 99%
“…Hens et al 23 have been opposed to 'full broad consent to any possible future research', especially for more sensitive research with more privacy risks, due to the child's right to express his own values. Furthermore, Giesbertz et al 24 have concluded that different biobank characteristics lead to a different involvement of children in the consent process. The OECD-Guidelines leave a broader consent open to national regulations, provided that additional safeguards are at hand, such as oversight mechanisms.…”
Section: Informed Consent For Donationmentioning
confidence: 99%
“…In the current study, we collected rabbit blood specimens with EDTA tubes and stored split aliquots at 4 C for different preservation durations. As for the reason we used rabbit blood specimens instead of human blood specimens in this study, it's that previous reports had shown that our biobank was established to focus on pediatric diseases (Gao et al, 2015), and human blood specimens collected from children are very valuable in a biobank related to pediatric diseases (Giesbertz, Bredenoord & Van Delden, 2015). Therefore, to observe the effects of preservation durations at 4 C of blood specimens on the quality of RNA from the whole blood and the leukocytes, we examined the purity, the integrity and gene expression of whole blood RNA and leukocyte RNA, after rabbit blood specimens were stored at 4 C for different preservation durations.…”
Section: Introductionmentioning
confidence: 99%